Introduction to Sexual Education Using Animated Video for Early Childhood - Dwi Rezky Anandari Sulaiman; M. Miftach Fakhri; Sanatang Sanatang; Shabrina Syntha Dewi; Irwansyah Suwahyu (PT. Global Research Collaboration, 2024)
Sex education for early childhood is a crucial step in preventing sexual abuse, particularly within an educational environment rooted in Islamic values. This program introduced sex education through animated videos at Al-Furqan Islamic Kindergarten, utilizing child-friendly and religiously appropriate educational media. Through an Action Research approach, the program was implemented in five stages: preparation, implementation, evaluation, reflection, and improvement actions. The results indicate that animated videos effectively enhanced children's understanding of self-protection and body boundaries. The program also alleviated parental concerns about the sensitive nature of the topic through their involvement in educational sessions and discussions, which helped create a supportive educational environment. Evaluation demonstrated a significant improvement in children's comprehension, while reflection provided valuable insights for continuous improvement, including developing a communication guide for parents. Overall, animated videos proved to be an effective method for introducing comprehensive sex education to young children, integrating Islamic values, and fostering collaboration between schools and families.